Asymptotically Periodic Solutions of Fractional Differential Equations - Henriquez-Miranda, H (Elsevier Inc., 2014)
We study the existence of pseudo S-asymptotically ?-periodic mild solutions for a class of abstract fractional differential equation. © 2014 Elsevier B.V. All rights reserved.